2020
DOI: 10.3390/min10110986
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Graphitized Coal Ash Char Concentrates as a Potential Synthetic Graphite Source

Abstract: Coal ash char concentrates from four countries (Portugal, Poland, Romania, and South Africa) were prepared, characterised, and graphitized under the scope of the Charphite project (Third ERA-MIN Joint Call (2015) on the Sustainable Supply of Raw Materials in Europe). Coal ash chars may be a secondary raw material to produce synthetic graphite and could be an alternative to natural graphite, which is a commodity with a high supply risk. The char concentrates and the graphitized material derived from the char co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…The recovered unburnt carbons are widely used for manufacturing a large number of premium carbon products, i.e., natural or synthesized nanostructured carbon materials and could fulfill the raw material demand of several carbon-based industries [165]. Until now, such recovered carbon particles from CFA were successfully used as an activated carbon, graphite substitutes [166], absorbents as well as adsorbents [167], lithium-ion batteries, supercapacitors [168,169], environmental remediation and protection [170], and solar cells. Moreover, there are a plenty of areas where carbon particles can be applied, but the major areas are shown above in Figure 5.…”
Section: Applications Of Cnms Unburned Carbon and Pahs Of Cfamentioning
confidence: 99%
“…The recovered unburnt carbons are widely used for manufacturing a large number of premium carbon products, i.e., natural or synthesized nanostructured carbon materials and could fulfill the raw material demand of several carbon-based industries [165]. Until now, such recovered carbon particles from CFA were successfully used as an activated carbon, graphite substitutes [166], absorbents as well as adsorbents [167], lithium-ion batteries, supercapacitors [168,169], environmental remediation and protection [170], and solar cells. Moreover, there are a plenty of areas where carbon particles can be applied, but the major areas are shown above in Figure 5.…”
Section: Applications Of Cnms Unburned Carbon and Pahs Of Cfamentioning
confidence: 99%
“…Previous studies have found that the ore-forming temperature of coal-to-graphite in nature is about 600-900 • C, whereas the experimental temperature of coal graphitization in the laboratory exceeds 2000 • C [19,89]. In order to decrease the activation temperature for synthetic graphite, previous researchers have tried to increase the pressure and add appropriate catalysts.…”
Section: Natural Catalytic Graphitization By Iron-bearing Mineralsmentioning
confidence: 99%
“…The treatment or utilization of coal ash was subject to coal ash properties, resulting primarily from the coal source and combustion process. Generally, the feed materials of the coal power plant have complex compositions, which are the mixture of coal collected from different areas based on the calorific value [ 4 ]. Furthermore, the behavior of inorganic constituents in combustion furnaces or other procedures has a strong effect on the apparent properties of ash particles, such as size, roughness, and combination, which concerns the possibility and ability of physiochemical separation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%